Literasi Kritis Dalam Pelajaran IPA Kelas V Sekolah Dasar - zahra; Khirjan Nahdi; Donna Boedi Maritasari (Fakultas Tarbiah Institut Agama Islam (IAI) Hamzanwadi Pancor, 2023)
This study aims to identify students’ critical literacy skills in science learning in the material of animal and human organs. This research was conducted at SDN 3 Suryawangi. The subjects in this study were 26 students in class V-B. The research method used is descriptive research method. Data collection techniques using observations and tests. Observations are used to collect data on teacher and student activities during the learning process. The test is used to measure students’ critical literacy skill. The results showed that the students in class V-B SDN 3 Suryawangi, Labuhan Haji District, obtained the result that the level of students’ critical literacy was determined by looking at 5 aspects of critical thinking indicators including giving simple explanations, building basic skills, concluding, giving further explanations, setting strategies and tactics. The ability of critical literacy in science lessons on animal and human movement organs shows that the level of critical literacy of students is categorized as sufficiently capable in the science learning process. This can be proven from the result which show the total number of student scores, namely 59, which is categorized as capable enough in the science learning process.